2000
DOI: 10.1016/s0928-8244(00)00153-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of de-O-acetylated serogroup C meningococci before the introduction of meningococcal serogroup C conjugate vaccines in the United Kingdom

Abstract: Meningococcal serogroup C conjugate (MCC) vaccines have been introduced in the UK to combat the rise in serogroup C meningococcal disease. Serogroup C meningococci may occur naturally expressing either O-acetylated (Oac(+)) or de-O-acetylated (Oac(-)) polysaccharide capsules. In a small study in the USA in the 1970s 15% of serogroup C meningococcal case isolates were reported to be Oac(-) though the prevalence of these Oac(-) isolates has not been recorded in the UK. This is of interest as the first MCC vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…Serogroup C isolates that were de-O-acetylated were phenotypically diverse [6] but the phenotypic similarity of O-acetylated W135 isolates suggests that these may be clonally related and capsular O-acetylation status may be stable within clones. Further work to genetically characterise these isolates is required [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serogroup C isolates that were de-O-acetylated were phenotypically diverse [6] but the phenotypic similarity of O-acetylated W135 isolates suggests that these may be clonally related and capsular O-acetylation status may be stable within clones. Further work to genetically characterise these isolates is required [21].…”
Section: Discussionmentioning
confidence: 99%
“…The serogroup C meningococcal polysaccharide capsule is a homopolymer of K-2C9-linked N-acetylneuraminic acid with acetyloxy groups exclusively bound to C7 and C8 of its sialic acid residues [4]. A small study in the USA found 15% of serogroup C isolates to be de-O-acetylated [5] while a larger UK study found the proportion to be 12% [6]. Studies utilising monoclonal antibodies (mAbs) indicate that serogroup C polysaccharide appears to express at least three di¡erent epitopes with di¡erent functional activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The vaccines against N. meningitidis were based on capsular polysaccharides (for serogroups A and C), which raise short-term T-independent protection and are ine¡ective in children less than 4 years old. A polysaccharide^protein-conjugated vaccine for serogroup C is in its ¢nal evaluation phase [1]. For serogroup B, the polysaccharide is not usable because of its very poor immunogenicity [2] and its antigenic cross-reactivity with human embryonic brain tissue [3].…”
Section: Introductionmentioning
confidence: 99%
“…Their licensure and distribution in October 1999 and March 2000, respectively, was followed by licensure in July 2000 of the Baxter vaccine (NeisVac-C ® ), which is a tetanus toxoid conjugate. The Baxter vaccine also differs in its polysaccharide component, which is made up of the de-O-acetylated polysaccharide expressed by some 12% of meningococcal C strains in the UK [34]. All three vaccines contain the same dose of polysaccharide antigen, 10 µg, and are considered interchangeable ( Table 1).…”
Section: Overview Of Meningococcal Group C Conjugate Vaccine Developmmentioning
confidence: 99%